2019
DOI: 10.1080/14786419.2019.1613395
|View full text |Cite
|
Sign up to set email alerts
|

Rhusflavanone and mesuaferrone B: tyrosinase and elastase inhibitory biflavonoids extracted from the stamens of Mesua ferrea L.

Abstract: Chemical isolation and bioactivity studies were conducted on the stamens of Mesua ferrea L., which are being used in a traditional skincare formulation in Myanmar. Rhusflavanone and mesuaferrone B were obtained as the main biflavonoids together with lupeol, five common flavonoids, and five phenolic compounds. After being identified by NMR and other spectroscopic analyses, these compounds were evaluated for their 1,1-diphenyl-2-picrylhydrazyl (DPPH)-radical scavenging, human leukocyte elastase inhibitory, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The docking results of these coupled compounds with the active site of 6LU7 showed the ∆Gbind and inhibition constants -11.91 kcal•mol −1 (Ki = 1.85 nM), -11.17 kcal•mol −1 (Ki = 6.52 nM) and -11.20 kcal•mol −1 (6.17 nM) respectively. The docking analysis of small molecules reflected typical interaction with MET49 residue (Samant et al, 2020) among our studied compounds, Mesuferrol (Zar et al, 2019), Mesuagin, Mesuabixanthone-A and Mammeigin showed interaction with MET49 but these interactions did not result in hydrogen bridge. Next, the selected compounds are subjected to test for various toxicity assessment parameters (Table 2).…”
Section: Resultssupporting
confidence: 59%
“…The docking results of these coupled compounds with the active site of 6LU7 showed the ∆Gbind and inhibition constants -11.91 kcal•mol −1 (Ki = 1.85 nM), -11.17 kcal•mol −1 (Ki = 6.52 nM) and -11.20 kcal•mol −1 (6.17 nM) respectively. The docking analysis of small molecules reflected typical interaction with MET49 residue (Samant et al, 2020) among our studied compounds, Mesuferrol (Zar et al, 2019), Mesuagin, Mesuabixanthone-A and Mammeigin showed interaction with MET49 but these interactions did not result in hydrogen bridge. Next, the selected compounds are subjected to test for various toxicity assessment parameters (Table 2).…”
Section: Resultssupporting
confidence: 59%
“…These triterpenoids are reported to have multiple biological functions, including modulation of leucocyte migration and neutrophil infiltration in the asthmatic lungs, antihistaminic activity, antiallergic activity, mast cells stabilisation, myeloperoxidase (MPO) inhibitory activity (Oliveira et al 2004, Okoye et al, 2014. Rhusflavanone and mesuaferrone B exhibit potent human leukocyte elastase inhibitory activity in in vitro studies (Zar Wynn Myint et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, rhusflavanone and mesuaferrone B are the anti-virulence components from M. ferrea with inhibitory activity on the secretion of effector proteins on Salmonella. Although, some researches have reported the diverse activity of biflavonoids (18,25,34,35), no anti-virulence activity has not been reported. Our results provide promising baseline information for the potential use of M. ferrea in the treatment of bacterial infections through anti-virulence pathway.…”
Section: Rhusflavanone and Mesuaferrone B Inhibited The Secretion Of mentioning
confidence: 99%
“…The dried flowers are used for fever, astringent, antiinflammation and also used in dysentery and antityphoid (8,9). In recent years, many bioactivities of M. ferrea were reported including antibacterial (8,(10)(11)(12)(13), antiarthritic (14), antioxidant and immunomodulatory (15), antispasmodic (16), estrogenic and progestational activity (17) and tyrosinase and elastase inhibitory activity (18). Our screening results on 93 Myanmar medicinal plants suggested that the flower extract of M. ferrea exhibited potent antibacterial and anti-T3SS activity (12).…”
Section: Introductionmentioning
confidence: 99%